الأدب الجزائري واستراتيجيات التنمية في ضوء العولمة - إبرير, بشير (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
This paper attempts to redraft the concept of literature in light off the findings of the communication and information sciences and the community’s dynamism that requires a set of capacities of values, knowledge, and aesthetics, which render the literary text looks meaningful and open to its reality as a mean of development. In other words, this is an attempt to research the relationship between literature and the social community with its diverse components that require a new type of literary practice totally different from the other social and economic practices that target the development. For this, we providea new analysis to the images of tourism inTaharOuettar’s novel” Al Zilzal” (the earthquake). Résumé: Cet article tend à la reformuler le concept de la littérature à la lumière des conclusions des sciences de l’information et de la communication et le dynamisme de la communauté nécessitant d’un ensemble de capacités de valeurs, de connaissances et d’esthétique qui font apparaitre que le texte littéraire est significatif et ouvert à sa réalité comme moyen de développement. En d’autres termes, ceci est une tentative de recherche de la relation entre la littérature et la communauté sociale avec ses diverses composantes qui requièrent un nouveau type de pratique littéraire tout à fait différent des autres pratique sociales et économiques visant le développement. Pour ce faire, nous avons fourni une nouvelle analyse des images du tourisme dans le roman de Tahar Ouettar « Al Zilzal » (Le tremblement de terre).